Pemanfaatan Web Design untuk Meningkatkan Pemasaran UMKM Buraunibaito dengan Blogger di Kota Padang - Adinda Rihhadatul Aisy; Ladiva Diti Ramadhani; Daffa Gusnadi; Sularno; Novadilatri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Web design has become a vital element in digital marketing, especially for SMEs like Buraunibaito, located on Jln. Edelweis Komplek Cimpago Permai II, Padang City. In this project, we applied the Project Based Learning (PBL) method to provide training on creating websites using Blogger, aimed at enhancing marketing and sales. Through observation and interviews, we collected information about this SME, including its history, products, and promotional strategies. The data obtained was used to develop a blog that includes background information, product photos, and pricing. As a result, Blogger serves as an interactive platform that allows SMEs to connect directly with customers and has the potential to function as an e-commerce site. By leveraging modern technology, Buraunibaito is expected to compete more effectively in the digital marketplace.